KINERJA MIKROBA Zymomonas mobilis DAN Saccharomyces cerevisiae UNTUK MENGURAIKAN HIDROLISAT TONGKOL JAGUNG MENJADI BIOETANOL DENGAN PENGARUH WAKTU FERMENTASI DAN RASIO PENAMBAHAN MIKROBA - Fatimah, Deralisa Ginting, Veronica Sirait (Universitas Sumatera Utara, 2017)
Bioethanol from biomass is one of energy which has a potential as alternative fuel. Bioethanol can be produced by using fungi or bacteria. The research was about the performance of Zymomonas mobilis and Saccharomyces cerevisiae to change corn cobs hydrolyzate into bioethanol by adding microbes to the influence of time and ratio of fermentation had been done. The hydrolyzate were decomposition of corn cobs using Trichoderma reesei and Aspergillus niger. The purpose of this study was to know the conversion of hydrolysis of corn cobs into bioethanol with variation time of fermentation (1 day, 3 days, 5 days, and 7 days) and rate of adding microbes (Zymomonas mobilis : Saccharomyces cerevisiae = 1:1; 1:2 and 2:1) (v/v). The glucose from corn cobs hydrolyzate was 5,869 g/ml. Fermentation wass carried out at 25 0C. Bioethanol which obtained from this study was investigated using gas chromatography. The optimum bioethanol yield was equal to 6,31% by using Zymomonas mobilis : Saccharomyces cerevisiae (2:1) and at the 3 days fermentation time.